2003
DOI: 10.1002/neu.10220
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells in the rat brain synthesize gonadotropin‐releasing hormone

Abstract: Mast cells occur in the brain and their number changes with reproductive status. While it has been suggested that brain mast cells contain the mammalian hypothalamic form of gonadotropin-releasing hormone (GnRH-I), it is not known whether mast cells synthesize GnRH-I de novo. In the present study, mast cells in the rat thalamus were immunoreactive to antisera generated against GnRH-I and the GnRH-I associated peptide (GAP); mast cell identity was confirmed by the presence of heparin, a molecule specific to mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…Other cells that have been reported to express GnRH and its mRNA are mast cells from the nervous system and the peritoneal cavity, as detected by immunohistochemistry and RT-PCR, respectively (Silverman et al, 1994; Gill and Rissman, 1998; Khalil et al, 2003). …”
Section: Gonadotropin-releasing Hormone (Gnrh)mentioning
confidence: 99%
“…Other cells that have been reported to express GnRH and its mRNA are mast cells from the nervous system and the peritoneal cavity, as detected by immunohistochemistry and RT-PCR, respectively (Silverman et al, 1994; Gill and Rissman, 1998; Khalil et al, 2003). …”
Section: Gonadotropin-releasing Hormone (Gnrh)mentioning
confidence: 99%
“…8 MCs are normal residents in the CNS 9,10 where they are found in close association with cerebral blood vessels during development and adulthood. 11,12 Brain MC numbers increase during neonatal development. 13,14 Our previous study demonstrated significant elevations of MC number and degranulation in association with neuronal injury at 48 hours after HI in the P7 rat.…”
mentioning
confidence: 99%
“…MCs, which play a notorious role in allergic inflammation, are also found in the CNS where they are concentrated in the brain parenchyma along the blood vessels and leptomeninges [11,12]. MCs produce a vast array of mediators, including proteases and vasoactive amines such as GnRH [13] and histamine [14]. MCs were reported to induce microglial activation and inflammatory mediator release in our previous studies [15,16], suggesting the pivotal role of MCs in the induction of CNS inflammation.…”
Section: Introductionmentioning
confidence: 99%